2018
DOI: 10.1186/s12954-018-0248-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cure: patient reported outcomes of hepatitis C treatment among people who inject drugs in Australia

Abstract: BackgroundRecent advances in the treatment of hepatitis C virus (HCV) infection provide the possibility of eliminating HCV as a public health threat. This focus on HCV elimination through treatment, however, is also driving a concomitant focus on ‘achieving cure’ as the primary outcome of treatment. The aim of this paper is to explore what people who inject drugs consider to be important in relation to outcomes of HCV treatment, and whether there are outcomes ‘beyond cure’ that might be important to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 37 publications
0
60
0
Order By: Relevance
“…However, findings from this survey suggest that the majority of PWID reported a positive impact on their ability to engage in wider society and explore new interests/hobbies after HCV treatment. Previous studies have also shown similar positive outcomes beyond HCV cure that are valued highly among PWID [ 16 , 31 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, findings from this survey suggest that the majority of PWID reported a positive impact on their ability to engage in wider society and explore new interests/hobbies after HCV treatment. Previous studies have also shown similar positive outcomes beyond HCV cure that are valued highly among PWID [ 16 , 31 ].…”
Section: Discussionmentioning
confidence: 66%
“…There is still a need to understand what motivates PWID to engage in care. Qualitative research has illustrated that eliminating the virus is not the only factor that motivates PWID to start therapy [ 31 ]. The results of our survey suggest that awareness of the availability of effective and well-tolerated treatments and the potentially severe consequences of untreated HCV are key motivators.…”
Section: Discussionmentioning
confidence: 99%
“…( 31 ) We also identified a need to increase awareness and understanding of the benefits of treatment with DAAs among patients, providers, and key stakeholders. ( 32 ) Some stakeholders perceived patients to be wary of treatment because of known historical side effects. Stakeholders suggested enlisting the help of peer educators ( 33 ) who can act as a bridge between the patient and provider, to increase motivation for treatment and to reduce self‐stigma among patients with HCV and provide encouragement to engage and comply with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study reported that PWUDs are seeking outcomes “beyond cure” including improved physical and mental health and positive changes in identity and social relationships. ( 37 )…”
Section: Discussionmentioning
confidence: 99%